Business Strategy of Multinational Trading Firm in Agriculture Sector: Case Study of Archer Daniels Midland Amid Pandemic and Geopolitical Conflict - Yusa, Muchammad Yustian; Aisyah, Sari Mutiara; Fadhlia, Maudy Noor (Andalas Institute of International Studies UNAND, 2023)
This research investigates how agricultural commodity trading companies formulate business strategies in response to pandemics and geopolitical conflicts. Using ADM (Archer Daniels Midland Company) as a case study, the study explores three key strategies: supply chain diversification, new market expansion, and risk mitigation. The research method involved analyzing ADM's annual reports and strategic actions during the COVID-19 pandemic and ongoing geopolitical conflicts. The theoretical framework is based on the concept of economics of commodity trading firms (Pirrong, 2014, 2015) and strategic management. The findings reveal that ADM effectively diversified its supply chain by securing raw materials from multiple global sources and investing in joint ventures and strategic partnerships. The company expanded into new markets through acquisitions and collaborations, thus broadening its business portfolio beyond agricultural commodities. Additionally, ADM's enterprise risk management (ERM) program helped mitigate risks related to operational efficiency, cyber-attacks, and geopolitical disruptions. The study concludes that ADM's comprehensive strategies not only minimized the adverse effects of external shocks but also positioned the company for sustainable growth. These strategies can serve as benchmarks for other companies in the agricultural sector to enhance resilience and contribute to sustainable development goals.